Factors Affecting the Incidence of Postpartum Blues in Postpartum Women in the Karang Tengah Urban Village Area, Sukabumi City - Rosdianto, Nuur Octascriptiriani (STIKep PPNI Jawa Barat, 2024)
Aims: This study was to determine the factors that influence the incidence of postpartum blues in postpartum mothers in Karang Tengah Urban Village, Sukabumi City. Methods: Correlational research with cross sectional approach. The study population was all postpartum mothers in Karang Tengah Urban Village, Sukabumi City and a sample of 30 people using purposive sampling technique. Results: There was an effect of social support, coping stress, socioeconomic status, and gender roles on the incidence of postpartum blues in postpartum mothers (p < 0.05). There is a simultaneous influence of social support, coping stress, socioeconomic status, and gender roles on the incidence of postpartum blues in postpartum women (p < 0.05). Conclusion: Postpartum blues incidence in postpartum mothers in Karang Tengah Urban Village Area of Sukabumi City is influenced by social support, coping stress, socioeconomic status, and gender roles.